Kanjuruhan Football Stampede (2022): Gaps in Disaster Preparedness and Response Mass-Casualty Management at A Mass Gathering Event - Yogadhita, Gde Yulian; Agustin, Widiana K; Atriana, Dinda (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: On October 1, 2022, a post-match crowd disturbance at Kanjuruhan Stadium in Malang gave rise to a mass-casualty incident, highlighting deficiencies in disaster preparedness and readiness of medical care teams who are responsive to potential disasters occurred soccer event. Objective: This paper analyses the Kanjuruhan tragedy within the framework of disaster preparedness and mass-casualty management using only data from the initial report and presentation slides. Methods: A qualitative case study based on the Joint Independent Fact-Finding Team report, media reports, and medical responders' testimonies in webinars, as well as an interview with a pre-hospital care coordinator. Data were thematically coded by 5 areas: risk assessment, medical readiness, events timeline, hospital response and coordination. Results: Spectator venues were fit for purpose from the athlete’s point of view but not so much from a spectators. No formal coordination system for command, evacuation, referral, communication between emergency medical service and hospital existed before the event. The use of tear gas caused problems with respiratory distress and crowd crush, while hospitals experienced a lack of patient coordination during influxes, poor triage and resource limitations. Conclusions: The event demonstrates major deficiencies in large-scale events and mass casualty management. Tougher regulations, unified command systems, compatible communications and risk-based planning can help prevent such catastrophes